Free Will versus Belief in Qadr? The Response of Sa‘id Nursi and its Modern Relevance - Awang Abd Rahman, Amilah (Afkar: Jurnal Akidah dan Pemikiran Islam, 2021)
The need of modern man requires more practical answer from religious perspective to support them in facing rapid changes and high demands of life. The issue of human will which is the most important and fundamental foundation to the concept of responsibility and morality is still open to discussion and debate. This paper aims at exploring the view of a reformer of Islam, Badiuzzaman Sa‘id Nursi in his 26th Word of his Risale-I Nur. Rather than having the discourse in a purely theological method, Nursi demonstrates it in a synthesis manner and suitable with modern man. The issue which is normally brought as juxtaposed with the concept of absolute will of God is dealt with in a harmonious way and suitable to all readers. Other than the phenomenological approach to the ontology of solving the relationship between God’s power and human will, Nursi also brought in very remarkable explanation about good and bad and how human should deal with them. Through-out his explanation, Nursi came with interesting illustrations and therefore successful in explaining the issue effectively. This suits his status as a reformer of Islam who came to shed lights on crucial issues with modern approach.